A clash of kings [compact disc, unabridged] - Martin, George R. R. (Martin, George R. R. Song of ice and fire, 2011)
Lord Eddard Stark and Robert Baratheon are dead, both victims of royal treachery. Chaos reigns in the wake of their deaths as six factions battle for the Iron Throne of the Seven Kingdoms.